Benefits of psychosocial support for adolescent mothers on infant development and maternal mental wellbeing in Rakai and Kyotera, Uganda: Quasi-experimental study - Esther Nakyaze; Mark Pesner; Marc Sklar; Eleanor Nakintu; Elizabeth B. Magill; Jolly Nankunda; Richard Kimaka; Daniel Murokora (PLoS ONE, 2025)
Twenty-four percent of Ugandan women give birth before the age of twenty, which is the highest proportion in East Africa. Recent literature shows that 65% of the adolescent pregnancies in Uganda are unplanned and unwanted. Due to cultural stigma, these adolescent mothers face significant challenges that may impact their mental wellbeing and their infants’ development. To address this gap, Babies and Mothers Alive Foundation collaborated with the Ugandan Ministry of Health to conduct the Mama Ambassador Program (MAP) research study from March 2019 to August 2020. The MAP was a fifteen-session group psychosocial intervention conducted monthly by trained community health workers. The sessions were implemented from the third trimester of pregnancy through twelve months after birth using a curriculum developed from the World Health Organisation (WHO’s) Care for Child Development manual, various maternal and infant guidelines and literature. This quasi-experimental study compared mothers and their infants who attended the fifteen-session group psychosocial intervention (group psychosocial support) at Rakai Hospital, with those receiving care as usual (antenatal, intrapartum and postnatal care) at Kalisizo Hospital. The outcomes studied included infant developmental outcomes at ages 2, 6, and 12 months using the Ages and Stages Questionnaire (ASQ) and maternal mental well-being at enrolment, birth, and 6 months post-partum using the WHO Self-Reporting Questionnaire (SRQ). The effect of the intervention was studied using difference-in-difference (DiD) analysis. A total of 789 adolescent mothers (446 in the intervention and 343 in the control group) were enrolled and of these, 84% of the mother-infant pairs completed all study measurements. The DiD estimations revealed that the intervention group outperformed the control group in all five ASQ infant development domains, with statistically significant results (p < 0.01) across 2–12 months: gross motor - mean difference (MD) 10.68 (SE = 1.42), fine motor- MD 8.55 (SE = 1.16), problem solving- MD 11.78 (SE = 1.46), communication- MD 6.05 (SE = 1.53), personal social- MD 15.42 (SE = 1.26). Furthermore, the intervention group showed increasing benefits over time, with scores at 6 months significantly higher than those at 2 months in all domains, and at 12 months, four of the five domains (except communication) showing significant improvements over 6-month scores. Additionally, adolescent mothers in the intervention group had significant improvements in their mental wellbeing towards birth and 6-months post-partum compared to the control group (p < 0.01), with a total reduction of 7.15 points in the mean score of mental health symptoms in the intervention group compared to an increase of 1.36 for those in the control group. In conclusion, a culturally adapted, group-based psychosocial support program targeting pregnant adolescents and implemented by community health workers in a resource-limited setting showed significant benefits for maternal mental wellbeing and infant developmental outcomes.